Open AccessOriginal Article Rising Incidence of Streptococcal Urinary Tract Infections: A Retrospective Clinical and Microbiological Assessment - Rasheed, Farhan; Yar, Ahmad; Afzal, Raja Kamran; Bilal, Muhammad; Jamil, Iqra; Ejaz, Asma (Pakistan Armed Forces Medical Journal, 2026)
Objective: To determine distinct species of Streptococci along with their antimicrobial susceptibility pattern in urine samples.Study Design: Retrospective Analytical Study.Place and Duration of Study: Department of Pathology, Allama Iqbal Medical College, Lahore, Pakistan, from Jan 21 to Mar 2023.Methodology: Urine samples of included subjects were processed according to standard microbiological procedures. Microscopy and culturing of urine were done. Organisms’ identification was done by different biochemical tests. AST was performed by the disc diffusion method according to CLSI guidelines.Results: Out of 7346 urine samples, 2377(32.4%) yielded growth. E. coli was most prevalent and yielded 957 (63.5%) positive results. Among 829 Streptococci spp., Enterococcus faecalis 492(59.3%) yields the highest number. The most effective antibiotics were found to be Vancomycin, Teicoplanin, and Nitrofurantoin.Conclusion: Unusual urinary isolates, including distinct streptococcal species, should be carefully monitored. Nitrofurantoin and Ceftriaxone showed high susceptibility rates and may be suitable for empirical UTI treatment.